Effect of progressive volume-based overload during plyometric training on explosive and endurance performance in young soccer players - Ramirez-Campillo, R.; Henriquez-Olguin, C.; Burgos, C.; Andrade, D. C.; Zapata, D.; Martinez, C.; Álvarez, C.; Baez, E. I.; Castro-Sepúlveda, M.; Peñailillo, L.; Izquierdo, M. (The Journal of Strength and Conditioning Research, 2015)
The purpose of the study was to compare the effects of progressive volume-based overload with constant volume-based overload on muscle explosive and endurance performance adaptations during a biweekly short-term (i.e., 6 weeks) plyometric training intervention in young soccer players. Three groups of young soccer players (age 13.0 ± 2.3 years) were divided into: control (CG; n = 8) and plyometric training with (PPT; n = 8) and without (NPPT; n = 8) a progressive increase in volume (i.e., 16 jumps per leg per week, with an initial volume of 80 jumps per leg each session). Bilateral and unilateral horizontal and vertical countermovement jump with arms (CMJA), 20-cm drop jump reactive strength index (RSI20), maximal kicking velocity (MKV), 10-m sprint, change of direction speed (CODS), and Yo-Yo intermittent recovery level 1 test (Yo-Yo IR1) were measured. Although both experimental groups significantly increased CMJA, RSI20, CODS, and endurance performance, only PPT showed a significant improvement in MKV and 10-m sprint time. In addition, only PPT showed a significantly higher performance improvement in jumping, MKV, and Yo-Yo IR1 compared with CG. Also, PPT showed higher meaningful improvement compared with NPPT in all (except 1) jump performance measures. Furthermore, although PPT involved a higher total volume compared with NPPT, training efficiency (i.e., percentage change in performance/total jump volume) was similar between groups. Our results show that PPT and NPPT ensured significant improvement in muscle explosive and endurance performance measures. However, a progressive increase in plyometric training volume seems more advantageous to induce soccer-specific performance improvements.